STUDY ON THE SOCIAL DISTANCING TOWARDS PEOPLE WITH MENTAL DISORDERS - Elena BUJOREAN (Association of Social and Educational Innovation, 2023)
Our study aimed to investigate the social distance towards people with mental disorders (MD). The ideational process marked by the concept of social distance led to equating this comcept with a lack of openness towards relating to other individuals, perceived to be different as a result of their inclusion in classes set apart from their own group, based on criteria judged to be correct. Thus, the objectives aimed to: • Assess the willingness to engage in befriending people with MD; • Assess the perception of the level of intelligence, trust and credibility given to people with MD in society and, in particular, in professional and couple relationships; • Identify perceptions on the causes of mental health problems, in particular, the extent to which there is individual responsibility for their occurrence; • Identify the extent to which people with MD are discriminated against in society. The study methodology consisted in the completion by the participants of a 12-item questionnaire - the Social Distance Scale (Link 1989). The group of subjects was made up of 329 students from different specializations, enrolled in the psycho-pedagogical training programme, undergraduate, and postgraduate courses.   Our study confirms that there is a need for more information on mental health issues, as it influences the degree of social distance. It is well-known that people with MD are subject to discrimination, and the consequences of stigma are visible both in accessing health services and in the quality of interpersonal relationships.